2011
DOI: 10.1007/s12243-011-0252-0
|View full text |Cite
|
Sign up to set email alerts
|

Satellite image compression by concurrent representations of wavelet blocks

Abstract: This paper proposes a complete compression and coding scheme for on-board satellite applications considering the main on-board constraints: low computational power and easy bit rate control. The proposed coding scheme improves the performance of the current Consultative Committee for Space Data Systems (CCSDS) recommendation for a low additional complexity. We consider post-transforms in the wavelet domain, select the best representation for each block of wavelet coefficients, and encode it into an embedded bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In [29], Delaunay has shown that the Lagrangian approach for selecting the best posttransformed block has two main drawbacks. First, the estimation of the required bit rate for ( ) is computationally intensive and not always accurate.…”
Section: Spatial Decorrelationmentioning
confidence: 99%
See 1 more Smart Citation
“…In [29], Delaunay has shown that the Lagrangian approach for selecting the best posttransformed block has two main drawbacks. First, the estimation of the required bit rate for ( ) is computationally intensive and not always accurate.…”
Section: Spatial Decorrelationmentioning
confidence: 99%
“…In [30], the posttransformed blocked coefficients are encoded by an adaptive arithmetic coding method. In [29], the posttransformed blocked coefficients are encoded by the bitplane encoding (BPE) method. However, the posttransforms destroy the zero-tree structure.…”
Section: Tucker Decomposition In Posttransform Domainmentioning
confidence: 99%
“…In [53], the bit-plane encoder (BPE) is used to encode both the posttransformed blocked coefficients and the side information. However, the posttransforms destroy the zero-tree structure; the PSNR using BPE is 0.2 dB less than using DWT and even worse at high bit rates.…”
Section: Proposed Algorithmmentioning
confidence: 99%
“…In [ 53 ], Delaunay et al have shown that the Lagrangian approach to select the best posttransformed block has two main drawbacks: (1) the bit rate estimation of encoding R ( f q b ) is computationally intensive and not always accurate; (2) the choice of the best posttransformed block depends on the quantization step q in the rate-distortion criterion. However, the coder does not define the quantization step when coding.…”
Section: Proposed Algorithmmentioning
confidence: 99%
See 1 more Smart Citation